Penerapan Model Pembelajaran Case Study pada Materi Aplikasi Maxwell Boltzmann - Pratiwi, Henny Indah (Journal of Management, Education and Communication, 2025)
The purpose of this study was to determine the application of the case study learning model in Maxwell Boltzmann Application material as an effort to improve the conceptual understanding of students in the physics study program at UIN Walisongo Semarang. The research method used was a one-group pretest-posttest. The technique used in data collection was a conceptual understanding test in the form of essay questions. The improvement in conceptual understanding was analyzed using a normality test (N-gain) to determine the learning outcomes before and after the treatment (pre-test and post-test) on the Maxwell Boltzmann Application material, particularly in the discussion of the Doppler effect. The results of this study indicate that there is a change between the pretest and posttest scores based on the normality test that was conducted using a case study model. The data obtained was moderate with a calculation of 0.47. This study shows that there is an increase in understanding of the Maxwell Boltzmann Application concept among students in the physics study program at UIN Walisongo Semarang